Development of a time-resolved fluorescence microsphere Eu lateral flow test strip based on a molecularly imprinted electrospun nanofiber membrane for determination of fenvalerate in vegetables - Zhang, Le; Zheng, Yiliu; Shao, Hua; Xiao, Ming; Sun, Jianchun; Jin, Maojun; Jin, Fen; Wang, Jing; Abd El-Aty, A. M.; She, Yongxin (Frontiers in Nutrition, 2022)
Fenvalerate residues in fruits and vegetables are the cause of biological immune system disorders. Existing sensor detection methods are harsh due to the shortcomings of antibody preparation and preservation conditions. Therefore, developing a recognition material with strong specificity, good stability, and low cost is of practical significance in designing a sensitive, simple, and rapid method. This study used the precipitation polymerization method to synthesize molecularly imprinting polymer (MIP). The MIP was prepared into a fiber membrane by the electrostatic spinning method, the fenvalerate hapten-mouse IgG-Eu fluorescent probe was synthesized, and the side flow chromatography strip was constructed to determine fenvalerate in vegetables using the immunocompetition method. The results showed that the adsorption capacity of MIP to fenvalerate was 3.65, the adsorption capacity of fenvalerate on MIPFM (electrospinning membrane containing the fenvalerate MIPs) was 5 times that of free MIP, and the test strip showed good linearity R2=0.9761 in the range of 50 μg/L-1000 μg/L. In conclusion, substituting fenvalerate monoclonal antibodies with a molecularly imprinted electrospinning membrane is ideal for rapid onsite detection of pyrethroids.